1985
DOI: 10.1007/bf00414768
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative degradation of resorcinol and resorcylic acids

Abstract: Abstract. Anaerobic fermentative degradation of resorcinol and resorcylates was studied in enrichment cultures inoculated with marine or freshwater sediments or digested sludge, e-Resorcylate (3,5-dihydroxybenzoate) was degraded very rapidly to acetate and methane by enrichment cultures inoculated with freshwater sediment or sewage sludge, but degradation was slow in enrichments from marine habitats. The freshwater cultures did not degrade any other related phenolic substrates. Inhibition of methanogenic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 27 publications
3
32
1
Order By: Relevance
“…All procedures for cultivation as well as for analysis of metabolic products were as previously described (Widdel and Pfennig 1981;Schink and Pfennig 1982;Tschech and Schink 1985). The mineral medium for enrichment and further cultivation was carbonate-buffered and sulfide-reduced, and contained trace element solution SLI0 (Widdel et al 1983), selenite-tungstate solution (Tschech and Pfennig 1984) and vitamin-solution (Pfennig 1978 Archives of Microbiology 145 (1986), pp.…”
Section: Cultivation Conditions and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All procedures for cultivation as well as for analysis of metabolic products were as previously described (Widdel and Pfennig 1981;Schink and Pfennig 1982;Tschech and Schink 1985). The mineral medium for enrichment and further cultivation was carbonate-buffered and sulfide-reduced, and contained trace element solution SLI0 (Widdel et al 1983), selenite-tungstate solution (Tschech and Pfennig 1984) and vitamin-solution (Pfennig 1978 Archives of Microbiology 145 (1986), pp.…”
Section: Cultivation Conditions and Chemical Analysismentioning
confidence: 99%
“…Pelobacter acidigallici (Schink and Pfennig 1982), and the same is true for trihydroxybenzenes. Resorcinol and resorcylic acids, with two hydroxy groups in meta-position to each other, are fermented to acetate and butyrate or acetate alone by defined cultures of strictly anaerobic bacteria; degradation does not always depend on a syntrophic cooperation with hydrogenscavenging anaerobes (Tschech and Schink 1985). Methanogenic degradation of catechol and hydroquinone proceeded in enrichment cultures via reductive dehydroxylation to phenol, and appeared to depend on syntrophic hydrogen oxidation (Szewzyk et al 1985).…”
mentioning
confidence: 99%
“…Primary enrichment cultures were initiated at the Geophysical Laboratory by adding about 1 ml inoculum (prepared by resuspending sediment material in 1 ml culturing medium) anaerobically to 10 ml of a modified version of the basal medium described by Slobodkina et al (2009b). The basal medium contained (l 21 distilled water): KH 2 PO 4 (0.33 g), (NH 4 ) 2 SO 4 (0.5 g), KCl (0.33 g), MgCl 2 ?6H 2 O (4.0 g), CaCl 2 ?2H 2 O (0.33 g), NaHCO 3 (0.8 g), NaCl (18.0 g), 1 ml trace-element solution SL-10 ( Sleat et al, 1984), 1 ml selenite-tungstate solution (Tschech & Schink, 1985) and 1 ml vitamin solution (Wolin et al, 1963). The pH of the medium was not adjusted and no reducing agent was added.…”
mentioning
confidence: 99%
“…1987) and Pelobacter acidigallici (Samain et al 1986), and a methyl viologen-dependent resorcinol reductase activity was found in a Clostridium sp. (Tschech and Schink 1985;Kluge et al 1990). Also a preliminary description of a nitrate reducer degrading resorcinol was presented recently (Kluge et al 1990).…”
mentioning
confidence: 99%